The influence of Wordwall educational game on students' learning interest in elementary school - Anggi Rozma Yusmita; Putri Octa Hadiyanti (Himpunan Pengembang Kurikulum Indonesia, 2025)
Learning media is one of the most essential elements in implementing learning activities, as it can convey messages to students through teaching resources and tools. This study aims to investigate the impact of using Wordwall media on the learning interest of fifth-grade elementary school students in the Water Cycle topic. The research employed a quantitative, quasi-experimental design. The study was conducted at SD IP YLPI Pekanbaru, involving 63 fifth-grade students divided into three classes: VA (21 students), VB (20 students), and VC (23 students). The sample consisted of an experimental class and a control class, each with 21 students. Data analysis techniques included tests, normality tests, t-tests, and hypothesis testing. The results indicate that Wordwall use significantly influences students' learning interest. This is evidenced by a notable difference between pretest and posttest scores in the experimental group. The findings suggest that Wordwall is an effective alternative medium for improving student interest in learning and assisting both teachers and students in overcoming learning challenges. Abstrak Media pembelajaran merupakan salah satu unsur terpenting dalam pelaksanaan kegiatan pembelajaran yang dapat menyampaikan pesan kepada siswa dalam bentuk sumber pembelajaran dan alat peraga. Penelitian ini bertujuan untuk mengetahui dampak penggunaan media Wordwall terhadap minat belajar siswa kelas V SD pada materi Siklus Air. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi-experimental. Subjek penelitian adalah siswa kelas V SD IP YLPI Pekanbaru yang berjumlah 63 siswa, terdiri dari tiga kelas: VA (21 siswa), VB (20 siswa), dan VC (23 siswa). Sampel penelitian dibagi menjadi kelas eksperimen dan kelas kontrol, masing-masing terdiri dari 21 dan 20 siswa. Teknik analisis data meliputi tes, uji normalitas, uji-t, dan uji hipotesis. Hasil penelitian menunjukkan bahwa penggunaan media Wordwall berpengaruh positif terhadap peningkatan minat belajar siswa. Hal ini terlihat dari adanya perbedaan signifikan antara nilai pretest dan posttest pada kelas eksperimen. Temuan ini menunjukkan bahwa Wordwall dapat menjadi media alternatif yang efektif dalam meningkatkan minat belajar siswa serta membantu guru dan siswa dalam mengatasi tantangan pembelajaran. Keywords: media pembelajaran; minat belajar; murid sekolah dasar; pembelajaran sains; Wordwall